1994
DOI: 10.1007/bf00241545
|View full text |Cite
|
Sign up to set email alerts
|

Postural adjustments in sitting humans following external perturbations: muscle activity and kinematics

Abstract: There are several controversies concerning the organization and induction of postural adjustments in standing humans. Some investigators suggest the responses are triggered by somatosensory inputs (especially from the ankle in standing subjects), while others emphasize the vestibular input induced by head acceleration. We examined postural responses in sitting subjects in order to describe the muscle activation pattern during various perturbations and to test whether somatosensory or vestibular stimulation eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(124 citation statements)
references
References 35 publications
7
112
1
2
Order By: Relevance
“…A central response, involving the central nervous system, as opposed to a stretch reflex, was suggested in a study monitoring the activity of lumbar extensors and neck extensors and flexors [4]. Later, Szabo and Welcher presented a study that supported the idea of a central response, and concluded that muscle activities in different parts of the body occurred at approximately the same time and were not dependent on acceleration or movement of that area of the body [23].…”
Section: Discussionmentioning
confidence: 99%
“…A central response, involving the central nervous system, as opposed to a stretch reflex, was suggested in a study monitoring the activity of lumbar extensors and neck extensors and flexors [4]. Later, Szabo and Welcher presented a study that supported the idea of a central response, and concluded that muscle activities in different parts of the body occurred at approximately the same time and were not dependent on acceleration or movement of that area of the body [23].…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes and sex differences in postural control adaptability Forssberg and Hirschfeld (1994) distinguished two functional levels involved in the development of postural control to externally triggered disturbances. The first level is the selection of basic postural synergies, and the second level is the regulation of basic synergies based on multisensory information.…”
Section: Evaluation Of the Developmental Process For Postural Controlmentioning
confidence: 99%
“…the epigenetically determined boundaries of direction speci-ficity. Direction specificity denotes the mechanism primarily to activate the muscles on the dorsal side of the body when the body sways forwards, and primarily to activate the ventral muscles when the body sways backwards 67 . Indeed, already before infants can sit independently, at 4 to 5 months, the postural activity of neck and trunk muscles is direction specific 44,64 .…”
Section: Selectionmentioning
confidence: 99%